Social isolation and academic self-efficacy as predictors of academic anxiety among Filipino undergraduate students. - Nicodemus, Maidy Nathalee U.
There are studies investigating the relationship between academics and anxiety, however, these do not provide insight into the current state of academic anxiety of undergraduate students in the Philippines. With this, this study aims to determine whether social isolation and its identified dimensions and academic self-efficacy predict academic anxiety among Filipino undergraduate students. A cross-sectional research design was employed, involving a sample of 307 Filipino undergraduate students from various universities in the Philippines. The data was collected through self-report measures assessing social isolation, academic self-efficacy, and academic anxiety. Statistical analyses, including a descriptive correlational design, and further analysis through multiple regression, were conducted to determine the predictive power of social isolation and academic self-efficacy on academic anxiety. The results revealed that social isolation (R2=.009, F=2.854, p=.092), and its dimensions: social network size (R2=.004, F=1.311, p=.253), frequency of social engagement (R2=.000, F=0.088, p=.767), and the quality of engagement with the social network (R2=.004, F=1.080, p=.299) did not predict academic anxiety; however, perceived social isolation, one of the subjective dimensions of social isolation was found to predict academic anxiety, although this deterministic relationship is very low (R2=.027, F=8.316, p=.004). Moreover, academic self-efficacy was found to be a predictor of academic anxiety (R2=.192, F=72.118, p=<.001). This study contributes to the literature by providing a better understanding of the contribution of academic self-efficacy to the academic anxiety experienced by Filipino undergraduate students. Furthermore, understanding the predictors of academic anxiety in this population will help inform interventions and support systems that promote mental well-being and academic success. Ultimately, this study will contribute to the development of effective strategies to mitigate academic anxiety in this context..
Research, Undergraduate, UPV Miag-ao, Bachelor of Science of Arts in Psychology
Keywords: Social isolation; Academic self-efficacy .; Social networks